'Powers of a squirrel, and also a girl': Squirrel Girl and alternatives for women in superhero comic-books – an interview with Ryan North. Issue 1 (1st July 2016) - Goodrum, Michael
Ryan North is a Canadian author who writes a host of comics, most notably Dinosaur Comics (www.qwantz.com, 2003-present), Adventure Time (2012–2014, winner of both an Eisner and a Harvey Award), The Midas Flesh (2013) and The Unbeatable Squirrel Girl (R. North and E. Henderson, 2015). North is also the creator of To Be Or Not To Be (2013), a choose-your-own-adventure version of Hamlet funded through Kickstarter, published as a book and also as a computer game. North has recently followed this with Romeo And/Or Juliet (2016).